2018
DOI: 10.1002/jcp.27028
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte‐to‐HDL‐cholesterol ratio as a prognostic marker in cardiovascular diseases

Abstract: Inflammation and lipid accumulation are two basic hallmarks of atherosclerosis as a chronic disease. Inflammation not only is a local response but can also be considered as a systemic process followed by an elevation of inflammatory mediators. Monocytes are a major source of proinflammatory species during atherogenesis. In atherosclerosis, modified low-density lipoproteins (LDLs) are removed by macrophages; these are recruited in the vessel wall, inducing the release of inflammatory cytokines in inflamed tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
188
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(209 citation statements)
references
References 72 publications
3
188
1
2
Order By: Relevance
“…In addition, as for single lipids, some lipid ratios could be well applied to predict CAD and the associations were of comparable magnitude [7]. For instance, the ratio of monocyte to highdensity lipoprotein cholesterol (HDL-C) (MHR) [8,9] and the ratio of low-density lipoprotein cholesterol (LDL-C) to HDL-C (LDL-C/HDL-C) were found to have correlation with poor prognosis in cardiovascular diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as for single lipids, some lipid ratios could be well applied to predict CAD and the associations were of comparable magnitude [7]. For instance, the ratio of monocyte to highdensity lipoprotein cholesterol (HDL-C) (MHR) [8,9] and the ratio of low-density lipoprotein cholesterol (LDL-C) to HDL-C (LDL-C/HDL-C) were found to have correlation with poor prognosis in cardiovascular diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Increased monocyte counts and decreased HDL-C levels have been reported to be associated with inflammatory disorders. Recently, monocyte to HDL-C ratio (MHR) has emerged as a novel and useful marker in different disease models, such as CAD, diabetes mellitus (DM), saphenous vein graft disease (SVGD) and acute ischemic stroke (AIS) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes are major source of pro-inflammatory and pro-oxidant cytokines (1,2). Monocytes interact with platelets and endothelial cells, which initiates pro-thrombotic and pro-inflammatory process (3).…”
Section: Introductionmentioning
confidence: 99%
“…High-density lipoproteins cholesterol (HDL-C) decreases atherosclerosis by inhibiting pro-inflammatory and pro-oxidant effects of monocytes (2,4). Hence, decreased of HDL-C and accumulation of monocyte may participate in CVD and atherosclerosis (1). Previous studies have reported that the monocyte-to-HDL ratio (MHR) increased in the inflammatory disorders (3,7), and atherosclerosis (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation